Why deep pockets make great borrowers: an empirical analysis of venture loans - Nico Lehnertz; Carolin Plagmann; Eva Lutz (Journal of Business Economics, 2022)
Startups typically have no positive cash flow, little collateral to offer, and high bankruptcy rates. As a result, they seem to be poor loan candidates. However, venture loans as hybrid form financing that include a loan and a warrant are used in practice. We focus on this distinct form of venture debt and identify characteristics of startups and their financing history that are related to their probability of receiving a venture loan. We use an unbalanced panel data sample of 13,540 companies that have conducted 27,577 financing rounds. Our key finding is that venture loans are associated with strongly committed existing investors, which stimulates the requirements of venture lenders and is signaled through large invested capital amounts per investor in previous rounds. Furthermore, we find that venture loans are associated with rather mature startups and offer empirical indication that the medical, health, and life science industry with clear milestones provides good conditions for venture loans.
Keywords: C23; G24; G32; M13; M21; 650; Venture lending; Venture debt; Venture loan; Venture capital